Two-Species Competition with High Dispersal: The Winning Strategy - S.A. Gourley; Yang Kuang (Mathematical Biosciences and Engineering)
This paper is motivated by the following simple question: how doesdiffusion affect the competition outcomes of two competing speciesthat are identical in all respects other than their strategies onhow they spatially distribute their birth rates. This may provideus with insights into how species learn to compete in a relativelystable setting, which in turn may point out species evolutiondirections. To this end, we formulate some extremely simple two-species competition models that have either continuous or discretediffusion mechanisms. Our analytical work on these modelscollectively and strongly suggests the following in a fastdiffusion environment: where different species have the same birthrates on average, those that do well are those that havegreater spatial variation in their birth rates. We hypothesizethat this may be a possible explanation for the evolution ofgrouping behavior in many species. Our findings are confirmed byextensive numerical simulation work on the models.